Enhancing the power quality in radial electrical systems using optimal sizing and selective allocation of distributed generations. - Bachirou Bogno; Deli Goron; Nisso Nicodem; S Shanmugan; Dieudonné Kidmo Kaoga; Kitmo; Akhlaque Ahmad Khan; Yasser Fouad; Michel Aillerie (PLoS ONE)
Optimizing energy resources is a major priority these days. Increasing household energy demand often leads to the deterioration of poorly sized distribution networks. This paper presents a method for energy compensation and optimization in radial distribution systems (ORDS). By integrating distributed generations (DG), an approach is used to evaluate voltage and power profiles, as well as power losses on radial distributed systems (PLRDSs). After integrating distributed generations, improved voltage and power profiles are established. A potential solution to power compensation and blackouts (PCB) can also be the use of hybrid distributed generation systems (HDGSs) that reinforce radial distribution networks (RDNs) by improving power quality. Accordingly, a proposed configuration system is shown in this work to inject multiple renewable energy sources (MRES) from selected regulated nodes. The feasibility of the proposed system is evaluated using particle swarm optimization (PSO), which was used to locate stable nodes and locations, sensitive to voltage fluctuations. The proposed approach is based on the evaluation of the power losses and voltage profiles of the IEEE 33 bus and IEEE 69 bus standards This MATLAB-based method establishes an objective function that converges more quickly to the optimal results.